Two-dimensional palladium diselenide for the oxygen reduction reaction - Koh, See Wee (2021)
The emerging two-dimensional (2D) materials, particularly 2D transition metal dichalcogenides (TMDs), show great potential for catalysis due to their extraordinary large surface areas and tuneable activities. However, the as-synthesized TMDs are usually chemically inert because of their perfect atomic structure and inaccessible interlayer space for electrolytes. Herein, we activate 2D palladium diselenide (PdSe2) for catalysing the oxygen reduction reaction using a controllable electrochemical intercalation process. The electrochemically activated PdSe2 exhibits greatly enhanced electrocatalytic activities such as a doubled current density, 250 mV positive shift of potential, 5 times smaller Tafel slope, and greatly improved stability. DFT calculations were employed to study the mechanisms of electrochemical activation. Complementary experimental and theoretical studies suggest that the significantly increased activities come from (1) the activated surface with enriched Se vacancies and chemically bonded oxygen, and (2) easy access of the interlayer space for reaction intermediates. Furthermore, the robustness of the Pd-Se bonding ensures high structural stability and excellent resistance to degradation.